A Framework for Project Time-Cost Optimization Considering Float Consumption Impact - Al Haj, Rana Ali (2012)
A Master of Science thesis in Civil Engineering by Rana Al Haj entitled, "A Framework for Project Time-Cost Optimization Considering Float Consumption Impact," submitted in January 2012. Thesis advisor is Dr. Sameh El Sayegh. Available are both soft and hard copies of the thesis.